The Impact of Customer Experience, Customer Value and Corporate Image on Customer Loyalty KRL Commuter Line - Kurniawan, Prena Ramadhita (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2024)
KRL Commuter Line Jabodetabek is a commuter train system that serves the Greater Jakarta area (abbreviation for Jakarta, Bogor, Depok, Tangerang and Bekasi). Managed by PT Kereta Commuter Indonesia (KCI), this line provides an important transportation link for millions of passengers every day. Several marketing variables can be maintained and improved, such as customer loyalty, so that it can reduce traffic congestion in Greater Jakarta. A quantitative approach strategy was used in this research method, which used IBM SPSS 25 for data analysis. To answer the research problem, data was collected through a survey using a questionnaire distributed to Jabodetabek KRL Commuter Line users. The results of the analysis show that the variables Customer Experience, Customer Value, and Corporate Image have a significant positive effect on Customer Loyalty.